Valdosta High School Scrapbook 8, April – June 1964 - Valdosta High School (My University, 1964)
This item is a collection of newspaper clippings detailing sports events and numerous stories about the marching band. Additionally the newspapers detail the final days of school for seniors graduating in addition to the colleges that will be attended by graduating seniors.
This item contains 1 PDF file with 23 Pages and a Title Page
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); Baseball; Basketball